Analysing TCP traffic congestion algorithms for wired links based on NS3 - Zhou, Weichen; Mohd Aman, Azana Hafizah; Attarbashi, Zainab; Azamuddin, Wan Muhammad Hazwan; Khaleel, Aymen Dheyaa (Semarak Ilmu, 2024)
An essential component of the Internet Protocol Suite is Transmission Control Protocol (TCP). In this article, the effectiveness of three distinct TCP congestion control algorithms, namely Reno, NewReno, and Cubic, in the context of wired lines has been examined. In a series of simulations, we changed the congestion control technique while maintaining the other parameters constantly using Network Simulator (NS3). With its distinctive fast recovery mechanism, TCP Reno has shown a strong ability to recover from packet losses quickly, cutting down on the time needed to go back to the highest attainable throughput. The TCP congestion control technique selected can have a big impact on a network's performance, notably in terms of throughput and stability. While our findings demonstrate major differences between the examined algorithms.